FMF-14 OPTIMUM WINDING TENSION AND NIP-LOAD INTO WOUND WEBS FOR PROTECTING WRINKLES AND SLIPPAGE(Flexible Media Feeding and Handling Machines IV,Technical Program of Oral Presentations) - Hiromu HASHIMOTO; Puttha JEENKOUR; Mongkol MONGKOLWONGROJN (My University, 2009)
This paper presented about the optimization technique (SQP) for wound roll in order to protect the problem of wrinkles and the slippage phenomena into wound roll. Regarding the optimum design, the objective function which includes tangential stresses and friction forces would be presented in this paper. Tangential stresses and radial stresses could be predicted by Hakiels nonlinear model. The friction coefficients could be calculated from air entrainment which was approximated by Hamrock and Dowson model as focusing on within nip-load. The design variables in this paper were winding tensions and were updated by the quadratic spline interpolation method. The optimum winding tension and nip-load condition from numerical results would be used for experimental. The study shows the results of the minimum air films between web layers, friction forces and the in-roll stress distributions in case of constant winding tensions, taper winding tension, and optimum winding tensions.
Keywords: Slippage; Tension (geology); NIP; Vibration and Dynamic Analysis